Chinese Bangka Identity through Khek Language Assimilation - Wijayanti, Nurvita; Fernanda, Andri; Ferianda, Sandy ((JELE) Journal Of English Language and Education, 2024)
This paper examines the presence of Chinese descendants on Bangka Island, focusing on assimilating the Khek language, spoken by the Hakka community, by studying the hybridization across four sub-districts: Pangkalpinang, Sungaliat, Muntok, and Belinyu. Using the qualitative methods, including interviews and recordings of daily conversations, this paper analyzes the linguistic choices and semantic shifts in Khek by discussing the characteristics of the Khek language. This study has two main objectives: (1) to identify the lexical patterns and meaning of the Khek language in everyday use, and (2) to explore the socio-historical factors influencing Khek’s development on Bangka island. Findings show significant language assimilation between Khek and Bangka Malay, shaped by the socio-historical interactions. This research contributes to understanding the linguistic assimilation process and the mutual influence of speech communities in a multilingual context, shedding light on the mutual influence of language communities and the preservation of linguistic identity amid assimilation.